The global underworld : transnational crime and the United States - Liddick, Don (International and comparative criminology., 2004)
Transnational crime is an increasing national security threat to the United States and to individual citizens around the world. Criminal groups both in the United Staes and abroad operate crime cartels that span national boundaries, but in ways that affect all Americans, and wreak havoc on law enforcement organizations as well as businesses and other entities, such as the stock market. More often than not, transnational crime takes the form of organized crime, and in its many forms is responsible for over-priced goods, unsafe products, environmental hazards, corruption of public officials, the.